Injection of Anti-proBDNF Attenuates Hippocampal-Dependent Learning and Memory Dysfunction in Mice With Sepsis-Associated Encephalopathy - Cui, Yan-Hui; Zhou, Shi-Fen; Liu, Yu; Wang, Shuang; Li, Fang; Dai, Ru-Ping; Hu, Zhao-Lan; Li, Chang-Qi (Frontiers in Neuroscience, 2021)
Sepsis associated encephalopathy (SAE) increases the risk of cognition and memory dysfunction, however, the mechanism is still unclear. Brain-derived neurotropic factor (BDNF) as the focus of attention for years has been known for its positive role in cognition and emotion regulation, however, the study of its precursor, proBDNF, is limited. This study aimed to elucidate the effects and associated mechanisms of hippocampal proBDNF in lipopolysaccharide (LPS) induced SAE mice model. In this study, we found that mice appeared cognition dysfunction and there were an obviously increase in the expression levels of proBDNF and its receptor, p75NTR in the hippocampus on the 7th day after LPS treatment. Meanwhile, the levels of BDNF and its receptors, TrkB, were decreased. Additionally, our results showed that proBDNF and p75NTR were mainly co-localized with neurons. Compared with the vehicle treatment, there was significant decrease in the number of neuron and Nissl bodies as well as the expression of GluR4, NR1, NR2A and NR2B in the hippocampus of SAE mice after LPS treatment. Furthermore, we found that LPS induced cognitive deficits would be ameliorated after anti-proBDNF antibody by intrahippocampal or intraperitoneal treatment, and the number of neuron and Nissl bodies as well as the expression of GluR4, NR1, NR2A, NR2B and PSD95 were significantly upregulated in the hippocampus of SAE mice after anti-proBDNF antibody intraperitoneal treatment. These suggested that proBDNF and its receptor, p75NTR, might play an important role in the pathophysiology of SAE.